Radio-localization of Non-Palpable Breast Lesions Under Ultrasonographic Guidance: Current Status and Future Perspectives - Follacchio, Giulia A.; Monteleone, Francesco; Meggiorini, Maria Letizia; Nusiner, Maria Paola; De Felice, Carlo; De Vincentis, Giuseppe; Liberatore, Mauro (Current Radiopharmaceuticals, 2017)
Background: Due to the spread of mammographic screening programs, a constant increase of clinically-occult breast cancer diagnosis has been registered. A correct approach to nonpalpable breast lesions requires an accurate intra-operative localization in order to achieve a complete surgical resection. The aim of this paper is to describe the state of the art of the US-guided procedures such as Radio-guided Occult Lesion Localization (ROLL) and Radio-guided Seed Localization (RSL) in comparison to the most widely adopted Wire-Guided Localization (WGL). Methods: Links to full text papers and abstracts published in the last 25 years regarding localization of non-palpable breast lesions were researched using PubMed service of US National Library of Medicine. Using the term “non-palpable breast lesions localization”, different localization techniques were considered and analyzed. Human studies, published in English, French, German, Italian, and Spanish in journals with an impact factor index, were taken into account, independently of the type of article (clinical trial, review, editorial, etc.) or radiopharmaceutical used. Since the aim was to assess the clinical value of the procedures, a higher relevance was assigned to studies with significantly high number of patients and to those comparing at least two localization techniques. The reliability of each technique was evaluated taking into account several parameters such as correlation index between two localization procedures, risk of complications, lesion margin involvement and rate re-operation. Conclusions: Since their introduction in clinical practice, several randomized clinical trials and meta-analyses showed the accuracy and reliability of radio-guided procedures performed under ultrasonographic guidance. ROLL and RSL offer a practical approach to the management of clinically-occult breast lesions.
Keywords: ROLL